Active Duty Military Learners and Distance Education: Factors of Persistence and Attrition. Issue 2 (2nd April 2020) - Volk, Fred; Floyd, Christopher G.; Shaler, Laurel; Ferguson, Lydia; Gavulic, Alyssa M.
ABSTRACT: Distance education is a rapidly expanding sector that is increasingly being utilized by military student populations due to its unique benefits and flexibility in terms of course options making it a more viable and attractive option. The present study aims to expand the current research on factors contributing to military distance learner's persistence in higher education. Using sample records from a sample of 2, 246 undergraduate students from a single large private Southeastern U.S. university's online program, a Classification Tree Analysis (CTA) was used to identify the breakpoints in predictive power of various predictors of academic persistence by military branch. Of specific interest was how the differing subgroups divided, in terms of persistence rate, based on factors, such as number of transcripts, age, prior academic performance, marital status, and rank. Results highlight how these factors differentially affect learners based on their respective branch of service.